A multiscale investigation of mechanical properties of bio-inspired scaffolds. Issue 13 (3rd October 2018) - Gu, Yucong; Yasodharababu, Mohan; Nair, Arun K.
Abstract: Finding a structural design which allows the scaffold to have a high porosity and large pore size while retaining high strength is essential. Here, a bio-inspired scaffold is designed based on the observed geometrical pattern of the apatite atomic crystal structure, and mechanical properties are compared with other common scaffold geometries. The bio-inspired scaffold design is proven superior using a multiscale computational approach, which combines density functional theory and finite element analysis to predict the stress reaction and substitution effects on the scaffolds. This study provides insight into better scaffold design using bio-inspired structures and the effect of substitutions.